1970
DOI: 10.3126/kumj.v8i1.3217
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and endoscopic spectrum of upper gastrointestinal manifestations in HIV patients

Abstract: Background: Human Immunodefi ciency Virus (HIV) infected patient frequently report upper gastrointestinal (GI) symptoms; however their prevalence and diagnostic approach is not well known. Objective: The objective of this study was to study clinical, endoscopic and histopathological changes in HIV infected patients with upper GI symptoms and their correlation with CD4 count. Materials and methods: We evaluated 50 HIV infected patients who presented to M.S. Ramaiah hospital with upper GI symptoms. All patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
4
1
Order By: Relevance
“…The commonest cause of esophageal symptoms was candidiasis, followed by cytomegalovirus infection which produced either diffuse esophagitis or discrete ulcerations (Wilcox and Saag, 2008). In the present study, weight loss was in 14% of HIV patients which was less than that reported by Ravikumar et al (2010) they found that weight loss was in 34% of HIV patients. This difference may be due to the fact that their pa samples suffered only from upper gastrointestinal symptoms.…”
Section: Discussioncontrasting
confidence: 63%
“…The commonest cause of esophageal symptoms was candidiasis, followed by cytomegalovirus infection which produced either diffuse esophagitis or discrete ulcerations (Wilcox and Saag, 2008). In the present study, weight loss was in 14% of HIV patients which was less than that reported by Ravikumar et al (2010) they found that weight loss was in 34% of HIV patients. This difference may be due to the fact that their pa samples suffered only from upper gastrointestinal symptoms.…”
Section: Discussioncontrasting
confidence: 63%
“…9 Clinically relevant VZV infections in HIV and AIDS patients involve the skin and central nervous system, whereas gastrointestinal involvement is rare. 9,15,16 Several studies examined HIV and AIDS patients with significant abdominal pain and found an overall low incidence of ulcers and no reported cases of VZV infection in the gastrointestinal tract upon endoscopic evaluation. [15][16][17][18] Myeloablative therapy in bone marrow and stem cell transplantation seems to predispose patients uniquely to gastritis caused by VZV.…”
Section: Discussionmentioning
confidence: 99%
“…However other studies done by Ravikumar et al, showed CMV esophagitis in two (4.87%). 12 Vui heng chong and Chee chain Lim et al, demonstrated CMV Esophagitis in 11.2%, herpes simplex esophagitis in 3.2%. 9 Endoscopic findings like oesophageal ulcerations, gastric erosions, intestinal tuberculosis which have been reported by other authors like Ravikumar et al, Vui heng chong and Chee chain lim et al, were not seen in our patients.…”
Section: Endoscopic and Histopathological Findingsmentioning
confidence: 97%
“…Other workers like Ravikumar et al, studied fifty patients, candidiasis was seen in 28%, esophagitis in 22% and Gastritis in 20%. 12 Vui heng chong and Chee chain lim et al, showed among one hundred twenty five HIV positive patients, candidiasis was seen in 23.1%. 9 Elshazly MA et al, 74% showed changes in esophagus and 28% in stomach.…”
Section: Endoscopic and Histopathological Findingsmentioning
confidence: 98%
See 1 more Smart Citation